Perancangan Dan Implementasi Teknologi Virtual Reality Modelling Language 3 Dimensi Pada Pengenalan Perangkat Keras Komputer Berbasis Website - Zaskia Wiedya Sahardevi; Oky Dwi Nurhayati; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
The purpose of this research is to design and implement the technology of Virtual Reality Modeling Language (VRML) 3D) on the introduction of computer hardware websites based. Steps design of multimedia applications for learning media computer hardware is done by performing data collection, literature review, analysis and system design followed by implementation and testing of the system. In this research using a black-box test method, where the acknowledgment is made to test the success of the exist functions. The result of the design of this application is a web based interactive applications in the desktop containing material computer hardware and visualized in 3D VRML form of a variety of input devices, output, processing, and storage devices. In addition, the animation demo mode petrified to get to know more computer hardware.